Caracterización de la comunicación como nudo critico para el desarrollo del trabajo en equipo en la empresa emrapah de Arenillas - Ariadel Mayanquer, Ariana Paulina (2016)
The main part of this research is attempting to identify existing conflicts as critical knot for the development of teamwork, it constantly arising in the members of the EMRAPAH company of canton Arenillas, province of El Oro, where taking of decisions, the exchange of ideas and lack of leadership always will cause discrepancy by the different points of view of the people who work in the company, due that the different forms of thinking can cause conflicts between colleagues. The importance of the roles played by social workers in the conflicts within the team work, are the main and fundamental basis to improve interaction, performance and individual perception of maturity in them and in them, also play an important role in determining the existence of what are their difficulties at the moment to disclose their performance and productivity offered by the company. Within an organization is important form a team of work, because the world requires that the society is involves for achieve a target end, where us goes to allow intervene, for characterize and observe it harmony, their skills, opportunities, threats and competencies, achieving so it responsibility of them members of them teams and by ende obtaining a good organization.